’n Deskriptiewe ondersoek na Sheila Cussons se poësievertalings aan die hand van Lefevere se sewe strategieë - Swart, Marius (Stellenbosch Papers in Linguistics Plus, 2015)
Opsomming Sheila Cussons word as een van die grootste Afrikaanse digters beskou. Melding van belangrike temas in haar oeuvre word algemeen in bestaande navorsing gemaak, byvoorbeeld oor vuur (De Villiers 1982), die visuele (Scholtz 1991), religieuse intertekste (Matthee 1984, Engelbrecht 2012), die bonatuurlike, goddelike of metafisiese (De Villiers 1984; Gilfillan 1984), asook die Katolieke en die mistieke in haar werk (Van Vuuren 1989), en die belang van metapoësie (Janse van Rensburg 1995). Kannemeyer (2005:453-459) verwys veral na Cussons se tegniese bedrewenheid en lig ook die “verwagtende uitsien na eenwording en die versmelting met God” (2005:457) as ’n sentrale motief in haar werk uit. Dit is egter nie so algemeen bekend of so omvattend nagevors dat Cussons ook in die 1980’s ’n bundel vertalings van haar eie poësie onder die titel Poems: a selection (1985) by Tafelberg gepubliseer het nie. Dié bundel bestaan uit seleksies uit haar bundels vanaf Plektrum (1970) tot by Membraan (1984) (Cussons 1985). In hierdie artikel, wat deel uitmaak van ’n meer omvattende ondersoek oor poësievertaling, word gepoog om deur ’n vergelykende lees van die Afrikaanse en Engelse gedigte in die bundel te bepaal of daar by Cussons ’n definieerbare “tipiese” vertaalstrategie of ‑strategieë afgelees kan word teen die agtergrond van Lefevere (1975) se beskrywing van sewe strategieë vir die vertaling van poësie. Daar word bevind dat Cussons se vertalings met sommige van Lefevere se strategieë ooreenstem, maar van ander geen blyke gee nie. Verder word daar in sekere vertalings strategieë aangewend wat nie onder Lefevere se raamwerk verklaar of ingedeel kan word nie, en in heelparty gevalle word daar op die oog af gewoon idiosinkraties vertaal. Ten slotte word aanvullings by Lefevere se model voorgestel vir die ontwikkeling van ’n vollediger raamwerk vir die bestudering van vertaalde Afrikaanse poësie. A descriptive investigation into the poetry translations of Sheila Cussons using Lefevere’s seven strategies Extended Abstract Sheila Cussons is generally seen as one of the great Afrikaans poets. Important subjects in her work include fire (De Villiers 1982), the visual (Scholtz 1991), religious intertexts (Matthee 1984; Engelbrecht 2012), the supernatural and metaphysical (De Villiers 1984, Gilfillan 1984) as well as Catholicism and mysticism (Van Vuuren 1989), and the importance of meta-poetry (Janse van Rensburg 1995). Kannemeyer (2005:453-459) notes her technical prowess and points out the expectation of becoming one with God as a central theme in her work. Cussons is also known for her translations of Borges’ stories into Afrikaans under the title of Die vorm van die swaard en ander verhale (1981). However, it is not as well known or well researched that she also published a volume of translated poems from her own work in the 1980s, entitled Poems: a selection (1985). This volume contains selections from her poetry from the titles Plektrum (1970) to Membraan (1984) (Cussons 1985). A descriptive investigation into the translations contained in Poems: a selection is offered in this article. According to Connoly, approaches to poetry translation often seem anecdotal and subjective (2001:170). This view is echoed by statements such as those likening poetry translation to playing a piano sonata on a trombone (Kelly and Zetzsche 2012:106), or descriptions of reading a translation as being like kissing through a veil or looking at the back of a tapissery (Bialik in Feinstein 2005:xvii). The challenging nature of poetry translation is also strongly implied by oft-cited quotes like that of Robert Frost, describing poetry as that which gets lost in translation (Bassnett 1998:57). Whether implicitly or directly put, the first, if not central question in numerous works on poetry translation seems to be whether poetry can be translated at all (Boase-Beier 2009:194). Nonetheless, poetry translation occupies a central position in the history of translation studies. Steiner’s seminal study After Babel (1975) essentially discusses the problems of poetry translation. Through the course of the 20th century a number of important works on poetry translation have also been published – examples include Raffel’s The art of translating poetry (1988), Robinson’s Poetry and translation. The art of the impossible (2010), Levý’s Umení prekladu (1963), published in English recently as The art of translation (2011), and Poetry translation as expert action (Jones 2011). For the purposes of this investigation, a component of a more comprehensive study of the realities and potentialities of Afrikaans poetry in English translation, it is assumed that poetry is indeed translatable, that poetry translation, per definition, brings about something that would not otherwise have existed, that poetry translation requires certain expertise, and that the study of translated poetry could yield valuable insights for translation studies and translator training. Therefore the investigation starts with one of the first sources attempting a structured discussion of possible strategies for poetry translation: Translating poetry – Seven strategies and a blueprint (Lefevere 1975). Fochi (2011) describes this text as one of the formative sources in linking methodological frameworks with translation criticism. She concludes that despite the relative age of the book, there is still much room for case studies testing its insights in different languages (Fochi 2011). This article attempts such a case study by considering translations by Sheila Cussons of her own poetry. The investigation is done by means of a descriptive and product-orientated reading against the backdrop of Lefevere’s seven strategies for poetry translation. The purpose of this reading, comprising a comparison of the Afrikaans and English poems in Poems: a selection in the context of Lefevere’s theory, is to determine whether a “typical” translation strategy or strategies can be identified in Cussons’ translations. Selections are made to illustrate Lefevere’s points as needed, rather than providing line-by-line discussions of poems. Methodological shortcomings are identified and suggestions for improvement and further study are made. Lefevere describes seven possible strategies for poetry translation. Firstly, phonemic translation (1975:19), in which a poem sacrifices some semantic meaning for the sake of sound retention. Cussons does not seem to make use of this kind of translation. Secondly, Lefevere refers to literal translation, where the sentence structure and meaning are put in a secondary position for the sake of retaining literal semantic equivalence (1975:27). This is nothing new in translation studies: Nabokov and many other scholars have held the opinion that a literal translation with accompanying notes is somehow more faithful or accurate, and therefore the preferred form (see for example Nabokov 1955). Cussons does not make use of this strategy either, although there are a few cases where the English translation does seem somewhat unidiomatic. Thirdly, Lefevere refers to metrical translation, where the metre is retained in translation (1975:37). This can difficulty in understanding the translation. Unsurprisingly, Cussons does not make use of this strategy at all. In fact, she often sacrifices a metrical attribute for the sake of semantic transfer. Similarly, she does not make use of (often somewhat forced) rhyming translations, Lefevere’s fourth strategy (1975:60), either. The fifth strategy, the free verse form, which can easily digress into merely “arbitrarily cut-up prose” (1975:61) is used rather extensively by Cussons, although without losing poetic structure as warned by Lefevere. She often seems to reimagine certain lines, sometimes adding or deleting others, but these changes are still absolutely minor (never adding or deleting more than one line) and not common at all (doing it only in 11 out of 37 poems). Lefevere’s last two strategies, the prose translation (1975:42-43) and the version/imitation (1975:76) are not used by Cussons in this volume. It would seem that Cussons’ translations do not show signs of all the possible strategies listed by Lefevere. Nonetheless, her translations also show certain strategies or mannerisms that cannot be classified using Lefevere’s model. The apostrophe is never used to indicate possessive forms – instead, the preposition “of” is used. Words containing religious or divine references are translated in a fashion pointing towards idiosyncrasy on the level of capitalisation. The format of four titles is adjusted and in a number of cases, meaning is explicated in the translation. Additionally, words related to fire and light, an important theme in the poet’s work, are translated in a fashion indicating a similar idiosyncratic strategy. It is worth noting that Lefevere does not work specifically in a context of self-translation in his 1975 book. Furthermore, the source and target cultures in his case (translations from Latin of poem 64 by Catullus by various translators) are probably much further removed than in the case of the Cussons poems (which, despite being English translations, were published by a South African publisher, with the Afrikaans source texts in the same volume). Nonetheless, this example of Lefevere’s work in systematising the study of poetry translation, as described above, provides a useful framework. In conclusion, it seems as though Lefevere’s strategies typically describe more significant changes than those apparent in Cussons’ translations, with the possible exception of “Christ of the burnt men” (Cussons 1985:32-33), which was cut and changed significantly. All of the other translations bear a very strong resemblance to their Afrikaans source texts on the levels of form, content and meaning. One could assume that it is rather more simple for the translator to follow the road mapped out by the poet, as Lefevere puts it (1975:103), when these roles are taken up by the same person. Lefevere’s strategies, however, do not offer a sufficient framework for fully describing these translations. In descriptive terms, one is left wanting, especially considering the description of the theoretical text as a “blueprint”. Although Lefevere is seen as a pioneer of the more systematic description of poetry translation, there are certain shortcomings in his classification which become apparent in a practical comparison of the English translations to the Afrikaans source texts. Certain translation strategies, such as the free verse form and the interpretation (versions rather than imitations, as shown above), are described and explained well. Other tendencies, such as capitalisation, microtextual changes and inconsistency, cannot be as readily classified in his framework. Of course, Lefevere himself expresses doubts about the use of a purely linguistic approach to translation analysis, since this could cause the investigator to get stuck on linguistic aspects of the given text only, and therefore also only the linguistic aspects of the translation process (1975:3). In my view, however, a more language-orientated approach in combination with Lefevere’s initial strategies could be of greater use than either of the two on their own in the descriptive study of poetry translation from Afrikaans into English. This hypothesis is expanded and tested in a forthcoming publication.